Dietary supplements and prostate cancer: A systematic review of double-blind, placebo-controlled randomised clinical trials - Posadzki, P; Lee, MS; Onakpoya, I; Lee, H; Ko, B; Ernst, E (2013)
Dietary supplements are popular among patients with prostate cancer (PC). The objective of this systematic review was to critically examine double-blind, placebo-controlled randomised clinical trials (RCTs) of non-herbal dietary supplements and vitamins (NHDS) for evidence that prostate specific antigen (PSA) levels were reduced in PC patients. Five databases were searched from their inception through December 2012 to identify studies that met our inclusion criteria. Methodological quality was independently assessed by two reviewers using the Cochrane tool. Eight RCTs met the eligibility criteria and were of high methodological quality. The following supplements were tested: isoflavones (genistein, daidzein, and glycitein), minerals (Se) or vitamins (vitamin D) or a combination of antioxidants, bioflavonoids, carotenoids, lycopenes, minerals (Se, Zn, Cu, and Mg), phytoestrogens, phytosterols, vitamins (B2, B6, B9, B12, C, and E), and other substances (CoQ10 and n-acetyl-l cysteine). Five RCTs reported no significant effects compared with placebo. Two RCTs reported that a combination of antioxidants, isoflavones, lycopenes, minerals, plant oestrogens and vitamins significantly decreased PSA levels compared with placebo. One RCT did not report differences in PSA levels between the groups. In conclusion, the hypothesis that dietary supplements are effective treatments for PC patients is not supported by sound clinical evidence. There are promising data for only two specific remedies, which contained a mixture of ingredients, but even for these supplements, additional high quality evidence is necessary before firm recommendations would be justified. © 2013 Elsevier Ireland Ltd.